GPS detection of total electron content variations over Indonesia and Thailand following the 26 December 2004 earthquake - Y. Otsuka (2018)
We report the response of the ionosphere to the large earthquake that occurred in West Sumatra, Indonesia, at 0058 UT on December 26, 2004. We have analyzed Global Positioning System (GPS) data obtained at two sites in Sumatra and at three sites in Thailand to investigate total electron content (TEC) variations. Between 14 and 40 min after the earthquake, TEC enhancements of 1.6-6.9 TEC units (TECU) were observed at subionospheric points located 360-2000 km north of the epicenter. From the time delays of the observed TEC enhancements, we find that the TEC enhancements propagated northward from the epicenter. The time delays between the earthquake and rapid increases in TEC, which occurred near the epicenter, are consistent with the idea that acoustic waves generated by the earthquake propagated into the ionosphere at the speed of sound to cause the TEC variations. A small TEC enhancement of 0.6 TECU was observed south of the epicenter, while no TEC enhancements were seen east of the epicenter. From a model calculation, we find that this directivity of the TEC variations with respect to the azimuth from the epicenter could be caused partially by the directivity in the response of the electron density variation to the acoustic waves in the neutral atmosphere. © 2006, The Seismological Society of Japan, Society of Geomagnetism and Earth, Planetary and Space Sciences, The Volcanological Society of Japan, The Geodetic Society of Japan, The Japanese Society for Planetary Sciences. All rights reserved.